Promoting Effective Education in Electromagnetics: Taiwan's School of Accessible and Visualized Electromagnetics Formed [Education Corner] - Liao, W. J.; Wu, R. B.; Wu, T. L.; Ma, T. G.; Pang, Y. H.; Tsai, Z. M.; Yu, H. H.; Tu, K. M.; Lin, H. C.; Peng, S. T. (IEEE Antennas and Propagation Magazine, 2016)
The School of Accessible and Visualized Electromagnetics (SAVE), a teaching and learning resource management consortium in Taiwan, has been formed to coordinate teachers from the field of electromagnetics (EM) to develop and share innovative teaching materials. Based on the cloud concept and following the simplicity, accessibility, visualization, and edutainment (S.A.V.E.) principles, various types of teaching resources, such as slides, problem sets, video clips, and interactive online laboratories, are available on the SAVE website for online learning. Teachers are able to customize a distinctive learning path to address the needs of a specific student group. To provide students with a means of evaluating their competence in EM, a large-scale online proficiency test was conducted concurrently at multiple sites. Analyses of test results and website uses are provided to assess the SAVE program performance and to draw future work topics.
Keywords: Computer science; Electromagnetics; Engineering education; Market research; Radio frequency; Resource management; SAVE Website; Web sites; __C:filed:1; computational electromagnetics; computer aided instruction; innovative teaching materials; large-scale online proficiency test; learning resource management consortium; online learning; school of accessible and visualized electromagnetics